Xrd Analysis Of Chemical Composition On Lead Surface Microelectrodes - Smejkal, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
This work is focused on the observation of changes in the chemical composition on thesurface of the negative electrode of the lead-acid battery using an XRD diffractometer. The measurementwas performed on thin pasted electrodes with a thickness of about 1mm. After the maturationand molding process, the fully charged negative electrode was gradually discharged andcharged at a rate of 0.2 C and 0.3 C. The negative electrode was analyzed at 100 %, 80 %, 60 %, 40% 20 % a 0 % SOC states. Chemical changes occurring on the surface of the negative electrode duringdischarging and charging of the lead-acid battery were measured using X-ray diffractometerRigaku MiniFlex HR 600.
Keywords: lead-acid; accumulator; negative electrode; X-ray diffractometer; morphology